Study on the Effect of Storage Conditions of Beauveria bassiana WP Formulations on its Survival Rate and Infectivity to Rice hispa, Dicladispa armigera (Olivier), Chrysomelidae Coleoptera - Purnima Das; L.K. Hazarika; K.C. Puzari; D. Bora; S. Ray (Contemporary Research and Perspectives in Biological Science Vol. 5, 2024)
The wettable powder formulation was developed by using the aerial conidia of the entomopathogenic fungus Beauveria bassiana. The insecticidal efficacy of the prepared formulation against two-day-old adult Rice hispa, Dicladispa armigera, was evaluated based on different storage temperatures. The shelf life of a talc-based wettable powder formulation of Beauveria bassiana (Bals.) Vuill. was tested at room temperature (24±1\(^°\)C), refrigerated conditions (4\(^°\)C), and in deep freeze conditions (–4\(^°\)C to –6\(^°\)C). At room temperature, the conidia remained viable for up to 180 days, maintaining a density of 20.22 × 107 conidia/gm and exhibiting 48% pathogenicity. In refrigerated conditions, viability extended to 210 days with the same conidial density, but pathogenicity increased to 69.45%. However, under deep freeze conditions, viability lasted for 300 days with the same conidial load, though pathogenicity dropped significantly to 20%.